Assessment of superconducting and structural stability of advanced Y-123 and Y-358 ceramics with Tb/Y substitution in main matrices - Güdücü, Gülnur; Öztürk, Özgür; Kurnaz, Sedat; Tokeşer, Elif Aşikuzun; Safran, Serap; Yıldırım, Gürcan (Elsevier BV, 2024)
In this study, the performances of Y1-x(Tb)xBa2Cu3O7-? (Y-123) and Y3-x(Tb)xBa5Cu8O18-? (Y-358) advanced ceramics prepared by sol-gel preparation route are investigated by the advanced characterization methods including X-ray diffraction (XRD), temperature dependent resistivity (?-T), vibrating sample magnetometry (VSM), scanning electron microscopy (SEM) and energy distribution spectroscopy (EDS) measurements and theoretical approaches. The EDS results illustrated that the Tb impurities were replaced successfully by the yttrium sites in the YBa2Cu3O7-y main matrix. Similarly, it was noted that the presence of excess impurities in the crystal structure led to the oxygenation problems. Electrical properties were determined by temperature dependent resistivity (?-T) measurements. ?-T results indicated that Tb doping reduced the critical transition temperature (Tc) values for the transition to superconductivity for all samples in two YBCO phases. Although it appears to have negative effects of Tb ions on the number of mobile charge carrier concentrations in the ? antibonding in-plane Cu-O bonds, bipolaron formations in the polarizable lattices, oxidation states, and amplitude of the pair wave function of both phases, the other valuable properties (morphology, crystallinity quality, interaction between adjacent layers, critical current density, and flux pinning ability) were noted to improve remarkably in the case of the optimum amount in the Y-123 superconducting phase. In this context, the Y-358 superconducting phase was harshly affected by the substitution due to the change of the ortorombicity, localization problem, impurity phases, structure stabilization, crystal structure quality, crystallization system, homogeneities of oxidation states, oxygen ordering degree, and impurity scatterings. Besides, the analysis of the fluctuation induced conductivity indicated that the Y-123 ceramics with longer c-axis coherence length and less anisotropic nature exhibited well superconducting properties. Additionally, the doping ratio of x=0.01 led to the formation and distribution of more nucleation centers for the thermal fluxon motions of 2D pancake vortices. Similarly, the optimum Tb doped Y-123 system exhibited much durable to applied field strengths due to the best interaction quality between grains. Accordingly, this study recommended that the Y1-x(Tb)xBa2Cu3O7-? advanced ceramic structure with new functionalities can find much more application areas in innovative, heavy-industrial technologies, and advanced engineering-related sectors. © 2024 Elsevier B.V.
Keywords: Advanced Y-123 ceramics; Y-358; Replacement; Fluctuation-Induced Conductivity; Pinning Force Ability